Efficacy of Early Childhood Professionals Teacher Post Implementation Program Activity Against Childhood Cognitive Development 4-6 Years (A Case Study in Pos Paud Mawar I Sragen) - Estirina, Rona; Adiarti, Wulan (Jurusan PGPAUD FIP UNNES, 2016)
Education is one form or means in advancing science for society. At an early age children begin to work both through formal and informal environments. The quality of education itself is not only derived from the infrastructure but also of professional and competent educators in the field. Quality education is not only derived from the infrastructure but also of readiness of the volunteers or educators. Readiness or can be called with efficacy For most people do not understand what it is about the efficacy of both globally and efficacy in the field of education. The aim of this study was to determine the efficacy of early childhood professionals Heading towards the development of a teacher of cognitive abilities of children aged 4-6 years in Pos PAUD Mawar I Ngrampal, Sragen. In this research, using qualitative research methods, case study approach. Data collection technique used observation, interview and documentation in collecting data. Data analysis techniques with interactive models by triangulation as a technique for data validity. Based on the results of efficacy studies ofÂ Pos PAUD professional teacherÂ Mawar I good enough that they can develop the cognitive abilities of students with a wide range of activities carried out by using the planning, implementation, evaluation and follow-up phases. The conclusion from this study is the efficacy of the Professional teacher Pos PAUD Mawar I of the program the organization of cognitive development Efficacy Professional teacher Pos PAUD Mawar I of the program activities of development of cognitive abilities indicated teachers to master the competence of educators by compose RKH, using various methods of learning, evaluating and assessment, establish communication or cooperation with communities, parents or fellow teachers.